Integrating SMEs into value chains: an accelerated growth plan for South Africa - Gongxeka, Ncebazimi (Graduate School of Business (GSB), 2021)
South Africa is listed among the world's top ten countries with the highest unemployment levels (World Bank, 2018). The National Development Plan (2013) envisioned that by 2030, 90% of new jobs in the country will be created by small and growing enterprises. Worryingly however, South Africa lags in meeting its target for job creation as set out in the National Development Plan despite some effort made by the government to promote and grow small businesses. Globally small and medium enterprises have been acknowledged for their key role in driving economic growth, job creation and poverty alleviation. Despite this important role, South Africa still has one of the highest small and medium enterprise (SME) failure rates in the world (Global Entrepreneurship Monitor, 2014). To circumvent this challenge, the South African government established development strategies including the notable Broad-Based Black Economic Empowerment (BBBEE) to drive the growth and expansion of small and medium enterprises (SMEs). BBBEE is intended to drive enterprise and supplier development (ESD) and improve the development and long-term growth of SMEs. Notably, large private corporations in South Africa have made significant investments in ESD; however many SMEs fail to survive past three years. This study therefore investigates the extent to which integration into a large corporate value chain promotes the sustainability of a SME. The study also examines the impediments that inhibit the growth of SMEs that are integrated in large corporate value chains. The research was conducted using an explanatory qualitative methodology. Five SME owners and six large corporate managers were interviewed to assess their perspectives and opinions on the SME-Corporate relationship. The research results concluded that corporate initiatives on ESD are of a significant benefit to SME growth, however challenges such as negative corporate perception and access to external funding remain a hindrance to SME growth. The study proposed recommendations to improve the successful integration of SMEs into corporate value chains.